2020
DOI: 10.1177/1747021820931096
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of metacognitive processing and executive function from childhood to older age

Abstract: The modern understanding of the term metacognition encompasses two levels of processing: a lower level awareness or knowledge of one’s own thoughts and a higher level regulation or control of our thinking. Metacognition, therefore, bears conceptual similarity with executive function: both are concerned with top-down monitoring and control of cognition in the service of ongoing goal-directed behaviour. Previous studies have shown a possible executive function advantage in multilingual speakers but also a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 75 publications
0
16
0
1
Order By: Relevance
“…In contrast, in a large web-based convenience sample there was no effect of age on local metacognitive efficiency in a staircased visual dot-discrimination task (Rouault et al, 2018b). Another performance-controlled study found trends towards a decline in metacognitive efficiency from mid-to late-adulthood (Filippi et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, in a large web-based convenience sample there was no effect of age on local metacognitive efficiency in a staircased visual dot-discrimination task (Rouault et al, 2018b). Another performance-controlled study found trends towards a decline in metacognitive efficiency from mid-to late-adulthood (Filippi et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…Within the children group, 77 were English monolinguals and 77 were bilinguals/multilinguals of different linguistic backgrounds enrolled in UK primary schools. Their parents completed an online questionnaire designed to establish demographic, socio-economic, and linguistic information ( Filippi, Ceccolini, Periche-Tomas & Bright., 2020 ; Filippi, Ceccolini, Periche-Tomas, Papageorgiou et al, 2020 ). All multilingual children started the acquisition of two or more languages with English being one of them either simultaneously from birth ( N = 59) or within the first 5 years of life ( N = 18).…”
Section: Methodsmentioning
confidence: 99%
“…Also, in the study that took as its starting point the conceptual similarity between metacognition and executive function (EF), it turned out that EF steeply declined with age, while metacognitive efficiency was preserved. Moreover, according to the exploratory factor analysis results, EF and metacognition are loaded by different factors across all ages (Filippi et al, 2020).…”
Section: Comparison Between Older and Young Adults In Terms Of Gf And Wmmentioning
confidence: 99%